(untitled) (Al-Qamar, 2019)
The purpose of this study is to analyze the different approaches to human rights from an Islamic and Western perspective. The horrific violation of rights during the Second World War forced world powers at the time to include the term human rights in the 1948 United Nations Charter, from which the international human rights system emerged as a universal declaration of human rights in 1948. The important difference is that the sources of human rights in Islam are divine revelation, but in the West the source of human rights is the human mind and experience. This article studies Islamic and United Nations Declaration’s perspectives on Human Rights. It finds that Islamic teachings on Human rights are more beneficial for humanity than the referred declaration.